2007
DOI: 10.1007/s11947-007-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion Studies of Aquaculture Feed using Distillers Dried Grains with Solubles and Whey

Abstract: Three isocaloric (3.5 kcal/g) ingredient blends containing 20, 30, and 40% distiller-dried grains with solubles (DDGS) along with 5% whey were prepared with a net protein content adjusted to 28% (wet basis [wb]). Other ingredients in the blends included soy flour, corn flour, fish meal, vitamin, and mineral mix. These blends were extruded in a single-screw extruder at 15, 20, and 25% (wb) moisture content and at 130 and 160 rpm screw speeds. Compared to previous research, the durability and unit density of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
60
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 30 publications
(28 reference statements)
12
60
0
5
Order By: Relevance
“…The more expended extrudates imply the more gelatinization of the starch component of the extruding blend which can result in a crispier and easier to digest extrudates (Rout, 1997). It is expected that, as the starch content is decreased, the obtained ER during extrusion is reduced as well (Chevanan et al, 2009). Obtaining a desired ER is one of the challenging issues when corn ethanol coproducts are used as the fishmeal replacers (Chevanan et al, 2009).…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%
See 3 more Smart Citations
“…The more expended extrudates imply the more gelatinization of the starch component of the extruding blend which can result in a crispier and easier to digest extrudates (Rout, 1997). It is expected that, as the starch content is decreased, the obtained ER during extrusion is reduced as well (Chevanan et al, 2009). Obtaining a desired ER is one of the challenging issues when corn ethanol coproducts are used as the fishmeal replacers (Chevanan et al, 2009).…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%
“…Furthermore, both physical and nutritional properties of the extruded aquafeed can vary depending upon the fish species. In terms of the physical properties, water stability, expansion ratio, and durability index of the extruded feed are very important (Chevanan et al, 2009;Rolfe et al, 2001;Wood, 1995). Generally, the more water stable the extruded feed, the longer the availability of the feed for fish.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rosentrater found that an increase in both moisture content and temperature result in a decrease in die pressure (Rosentrater et al, 2009a,b). Chevanan found that increasing the moisture content resulted in an increase in pellet durability (Chevanan et al, 2007a). They also found that increasing the temperature resulted in a decrease in apparent viscosity and pellet durability.…”
Section: Introductionmentioning
confidence: 96%